2007
DOI: 10.1525/sop.2007.50.1.27
|View full text |Cite
|
Sign up to set email alerts
|

Does Social Capital Still Matter? Immigrant Minority Disadvantage in School-Specific Social Capital and its Effects on Academic Achievement

Abstract: Using the National Education Longitudinal Study of 1988, the authors examine the determinants of social capital and its effects on school achievement for minority and immigrant students. The authors use two measures of social capital-intergenerational closure and parentschool involvement-and distinguish minority groups by generational status. Results indicate that compared to third-generation White students, immigrant Asians and Hispanics and third-generation Black students possess less social capital. Minorit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
133
4
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 157 publications
(143 citation statements)
references
References 40 publications
(79 reference statements)
5
133
4
1
Order By: Relevance
“…Parent-school involvement and inter-generational closeness have been found to be positively related to the education outcomes of children of immigrants, benefitting measures such as average grades or tests scores (Kao & Rutherford, 2007) or preventing certain types of behaviour by the second-generation, such as truancy (McNeal, 1999).…”
Section: Family Involvement and Educational Achievementsmentioning
confidence: 99%
“…Parent-school involvement and inter-generational closeness have been found to be positively related to the education outcomes of children of immigrants, benefitting measures such as average grades or tests scores (Kao & Rutherford, 2007) or preventing certain types of behaviour by the second-generation, such as truancy (McNeal, 1999).…”
Section: Family Involvement and Educational Achievementsmentioning
confidence: 99%
“…The positive impact of social capital on educational achievement is confirmed by several empirical studies [37,54,55]. Similarly various studies found evidence for the thesis, that immigrants have lower levels of social capital [56][57][58]. Reyneri and Fullin [59, page 35] explicitly state: "The fact that highly educated second generation immigrants still suffer serious labour market disadvantages has been ascribed just to their lack of host country-specific social capital."…”
Section: Macrosocietal Logics Of Educational Stratificationmentioning
confidence: 84%
“…This indicates that migration status in these countries is an indicator for lacking social integration (social capital) (cp. [56][57][58][59]). Remarkably, the traditional immigration countries show the lowest degrees of inequality based on migration background.…”
Section: Patterns Of Educational Inequality In 30 Industrialisedmentioning
confidence: 99%
“…Researchers have noted the importance of social support and social networks during migration (e.g., Bankston & Zhou, 2002;Kao & Rutherford, 2007;McKether, 2008). Ornelas, Perreira, Beeber, and Maxwell (2009) found that immigrant mothers experiencing stress and other emotional problems used social networks and community resources to promote resilience.…”
Section: Immigrant Women and The Migration Processmentioning
confidence: 99%